Synthesis and antimicrobial evaluation of two peptide LyeTx I derivatives modified with the chelating agent HYNIC for radiolabeling with technetium-99m. Issue 1 (December 2016) - Fuscaldi, Leonardo; dos Santos, Daniel; Pinheiro, Natália; Araújo, Raquel; de Barros, André; Resende, Jarbas; Fernandes, Simone; de Lima, Maria; Cardoso, Valbert
Abstract Background Current diagnostic methods and imaging techniques are not able to differentiate septic and aseptic inflammation. Thus, reliable methods are sought to provide this distinction and scintigraphic imaging is an interesting option, since it is based on physiological changes. In this context, radiolabeled antimicrobial peptides have been investigated as they accumulate in infectious sites instead of aseptic inflammation. The peptide LyeTx I, from the venom ofLycosa erythrognatha, has potent antimicrobial activity. Therefore, this study aimed to synthesize LyeTx I derivatives with the chelating compound HYNIC, to evaluate their antimicrobial activity and to radiolabel them with99m Tc. Methods Two LyeTx I derivatives, HYNIC-LyeTx I (N-terminal modification) and LyeTx I-K-HYNIC (C-terminal modification), were synthesized by Fmoc strategy and purified by RP-HPLC. The purified products were assessed by RP-HPLC and MALDI-ToF-MS analysis. Microbiological assays were performed againstS. aureus (ATCC® 6538) andE. coli (ATCC® 10536) in liquid medium to calculate the MIC. The radiolabeling procedure of LyeTx I-K-HYNIC with99m Tc was performed in the presence of co-ligands (tricine and EDDA) and reducing agent (SnCl2 . 2H2 O), and standardized taking into account the amount of peptide, reducing agent, pH and heating. Radiochemical purity analysis was performed by thin-layer chromatography on silica gel strips and the radiolabeled compound was assessed by RP-HPLC and radioactivity measurement of the collected fractions. Data were analyzed by ANOVA, followed by Tukey test (p -values < 0.05). Results Both LyeTx I derivatives were suitably synthesized and purified, as shown by RP-HPLC and MALDI-ToF-MS analysis. The microbiological test showed that HYNIC-LyeTx I (N-terminal modification) did not inhibit bacterial growth, whereas LyeTx I-K-HYNIC (C-terminal modification) showed a MIC of 5.05 μmol. L−1 (S. aureus ) and 10.10 μmol. L−1 (E. coli ). Thus, only the latter was radiolabeled with99m Tc. The radiochemical purity analysis of LyeTx I-K-HYNIC-99m Tc showed that the optimal radiolabeling conditions (10 μg of LyeTx I-K-HYNIC; 250 μg of SnCl2 . 2H2 O; pH = 7; heating for 15 min) yielded a radiochemical purity of 87 ± 1 % (n = 3). However, RP-HPLC data suggested99m Tc transchelation from LyeTx I-K-HYNIC to the co-ligands (tricine and EDDA). Conclusions The binding of HYNIC to the N-terminal portion of LyeTx I seems to affect its activity against bacteria. Nevertheless, the radiolabeling of the C-terminal derivative, LyeTx I-K-HYNIC, must be better investigated to optimize the radiolabeled compound, in order to use it as a specific imaging agent to distinguish septic and aseptic inflammation.